Investigating the Relationship Between Metacognitive Awareness and Critical Reading Performance among Undergraduate EFL Students - Nabila Syahrani; Nella Yuadiah Ningsih; Siti Ananda Zalzabila Mudjarab; Munir (Universitas Islam Negeri Palopo, 2026)
This study investigates the relationship between metacognitive awareness and critical reading performance among undergraduate EFL students in Indonesia. The research addresses the need to better understand how students’ awareness of reading strategies contributes to their ability to engage in higher-order reading processes. A quantitative correlational research design was employed, involving 150 undergraduate students from the English Education program at UIN Alauddin Makassar. Data were collected using the Metacognitive Awareness of Reading Strategies Inventory-Revised (MARSI-R) to measure students’ metacognitive awareness and a researcher-developed critical reading test consisting of 25 multiple-choice items to assess critical reading performance. The data were analyzed using Pearson Product-Moment Correlation. The results revealed a statistically significant and strong positive relationship between metacognitive awareness and critical reading performance (r = 0.971, p < 0.01), indicating that students with higher levels of metacognitive awareness tend to achieve better results in critical reading tasks. These findings suggest that metacognitive awareness plays an important role in supporting students’ ability to analyze, evaluate, and interpret texts effectively. The study highlights the importance of integrating metacognitive strategy instruction into reading pedagogy to enhance students’ critical reading skills. However, the findings are limited to the specific context of this study and should be interpreted within its scope. Future research is recommended to explore additional variables and employ different research designs to further examine this relationship.